A Systematic Search and Review of Adult-Targeted Overweight and Obesity Prevention Mass Media Campaigns and Their Evaluation: 2000–2017. Issue 2 (1st February 2018) - Kite, James; Grunseit, Anne; Bohn-Goldbaum, Erika; Bellew, Bill; Carroll, Tom; Bauman, Adrian
Abstract : Mass media campaigns are a commonly used strategy in public health. However, no review has assessed whether the design and evaluation of overweight and obesity campaigns meets best practice recommendations. This study aimed to fill this gap. We systematically searched five databases for peer-reviewed articles describing adult-targeted obesity mass media campaigns published between 2000 and 2017, complemented by reference list searches and contact with authors and agencies responsible for the campaigns. We extracted data on campaign design, implementation, and evaluation from eligible publications and conducted a qualitative review of 29 publications reporting on 14 campaigns. We found a need for formative research with target audiences to ensure campaigns focus on the most salient issues. Further, we noted that most campaigns targeted individual behaviors, despite calls for campaigns to also focus upstream and to address social determinants of obesity. Television was the dominant communication channel but, with the rapid advance of digital media, evaluation of other channels, such as social media, is increasingly important. Finally, although evaluation methods varied in quality, the evidence suggests that campaigns can have an impact on intermediate outcomes, such as knowledge and attitudes. However, evidence is still limited as to whether campaigns can influence behavior change.